Educational Communication for Adults in Quranic Literacy in East Kutai - Azhar, Azhar; Aminah, Siti; Mukhtar, Mukhtar; Gumilang, Randi Muhammad; Alfiyanto, Afif (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2023)
In attempts to address issues in the realm of Islamic education, particularly at the adult community level, al-Quran literacy is frequently raised. Although adults are supposed to be reasonably literate in the Al-Quran, there is nevertheless a disconnect with the reality of societal conditions. It is important to give careful consideration to the process of teaching adults Al-Quran literacy through education. In order to provide individuals in East Kutai with an instructional communication method for Al-Quran literacy, this research attempts to do so. This study employs descriptive methodology and is classified as a qualitative study. According to the study's findings, adult education programs in Al-Quran literacy in East Kutai use persuasive, dialogic, and demonstrative communication styles. The government, social environment, and family environment all provide impetus for the Al-Quran literacy process. In terms of techniques, the iqro method is employed in the educational process to facilitate adult learners' comprehension of the Qur’an. In addition, an environment free from coercion and a feeling of community among adults without literacy in the Qur'an are supportive elements in the process of achieving Qur’an literacy. In the meantime, adult physical condition, a lack of infrastructure and support systems, and a comparatively short study period are the things impeding Al-Quran knowledge.